RELATIONSHIP MARKETING: THE CASE OF BETTERLANGUAGES.COM LTD - Aitken, Laura K. (2011)
This study will examine Relationship Marketing within B2B services, focusing on the translation agency Betterlanguages.com Ltd as a case in point. Betterlanguages.com Ltd is a small translation agency based in the East Midlands that currently specialises in label and packaging translation for high-street retailers. As they operate in a niche market the use of a case study will be the best suited approach to explore how their business functions and for researcher to produce a study that will be of use to the company. The objectives of this study are twofold; firstly, to examine the relationships between Betterlanguages.com Ltd and their clients, with a focus on how relationships are developed maintained. Secondly, to recommend Relationship Marketing strategies through which customers’ relationships can be strengthened and customers retained in the long run by Betterlanguages.com Ltd, and potentially other B2B service firms.